Ответы и объяснения

2014-02-24T20:55:15+04:00
1) 2sin(x/3)cos3x=cos3
2sin(x/3)cos3x-cos3x=0
cos3x(2sin(x/3)-1)=0
cos3x=0                           2sin(x/3)-1=0
3x=pi/2+pi*n                      sin(x/3)=0.5
x=pi/6+pi*n/3                     x/3=pi/6+pi*n
                                        x/3=5pi/6+pi*n
                                        x=pi/2+6pi*n                                         
                                        x=5pi/2+6pi*n

 Второе решаешь по такому же принцыпу, только там  синус выносишь и раскладиваешь